1985
DOI: 10.3109/10641968509073588
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Inhibitors Specific for Human Renin

Abstract: Seven active tetrapeptide amides characterized by a C-terminal phenylalanyl aminoadamantane (PheNHAd) sequence, were identified by selective testing for human renin inhibitory activity among compounds with adjacent hydrophobic groups and molecular size equivalent to 3-5 amino acid residues. The new inhibitors were compared with known renin inhibitors (RIP, pepstatin, H-77) and opioid analgesic agents (Met-enkephalin, morphine), with the following results: The new inhibitors were active against human renin (IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In particular, 1-adamantanamine derivatives like 301 (Scheme 44) were found to produce central and peripheral opioid activities. 616 Another study focusing on the development of peptidic inhibitors for human renin 618 reported adamantane substituted peptides that also displayed high affinities to opiate receptors. The 2-adamantylamino derivative 302 displayed an IC 50 of 1.9 · 10 −10 M in a radioligand binding assay using rat brain homogenate.…”
Section: Other Targets In the Cnsmentioning
confidence: 99%
“…In particular, 1-adamantanamine derivatives like 301 (Scheme 44) were found to produce central and peripheral opioid activities. 616 Another study focusing on the development of peptidic inhibitors for human renin 618 reported adamantane substituted peptides that also displayed high affinities to opiate receptors. The 2-adamantylamino derivative 302 displayed an IC 50 of 1.9 · 10 −10 M in a radioligand binding assay using rat brain homogenate.…”
Section: Other Targets In the Cnsmentioning
confidence: 99%